2023
DOI: 10.7554/elife.82450
|View full text |Cite
|
Sign up to set email alerts
|

ARPC5 isoforms and their regulation by calcium-calmodulin-N-WASP drive distinct Arp2/3-dependent actin remodeling events in CD4 T cells

Abstract: CD4 T cell activation induces nuclear and cytoplasmic actin polymerization via the Arp2/3 complex to activate cytokine expression and strengthen T cell receptor (TCR) signaling. Actin polymerization dynamics and filament morphology differ between nucleus and cytoplasm. However, it is unclear how the Arp2/3 complex mediates distinct nuclear and cytoplasmic actin polymerization in response to a common stimulus. In humans, the ARP3, ARPC1, and ARPC5 subunits of the Arp2/3 complex exist as two different isoforms, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 65 publications
(90 reference statements)
0
5
0
Order By: Relevance
“…The reported defects, resulting in combined immunodeficiencies with severe inflammation and early-onset autoimmunity, inflammation, and mortality, highlight the clinical relevance of Arp2/3 complex dysfunction (64)(65)(66). Notably, isoform diversity within the Arp2/3 complex may determine cellspecific phenotypes (67,68), prompting further exploration of individual ARPC isoforms for MC biology.…”
Section: Discussionmentioning
confidence: 99%
“…The reported defects, resulting in combined immunodeficiencies with severe inflammation and early-onset autoimmunity, inflammation, and mortality, highlight the clinical relevance of Arp2/3 complex dysfunction (64)(65)(66). Notably, isoform diversity within the Arp2/3 complex may determine cellspecific phenotypes (67,68), prompting further exploration of individual ARPC isoforms for MC biology.…”
Section: Discussionmentioning
confidence: 99%
“…Actin remodeling in response to T cell receptor (TCR) engagement was monitored by forming circumferential F-actin rings as previously described [ 61 , 62 ]. In brief, stimulatory coverslips were prepared by coating with a 0.01% poly-L-lysine (PLL; Sigma) solution for 10 minutes at room temperature, followed by wet-chamber incubation for 3 hours at 37°C with 7 μg/ml anti-CD3 antibody (50 μl per coverslip, clone HIT3a against CD3E; BD Biosciences) in phosphate-buffered saline (PBS).…”
Section: Methodsmentioning
confidence: 99%
“…CYTOR RNA levels were normalized to the gapdh gene. Although we are aware that GAPDH expression is elevated following TCR stimulation, we did analyze several cellular genes in search of a better marker, but concluded that, e.g., genes for actin polymerization machinery are all affected more strongly by T cell activation than gapdh [ 62 ]. We therefore used gapdh for normalization.…”
Section: Methodsmentioning
confidence: 99%
“…To address this, we first used ProDOL in combination with CoPS to determine the absolute SLP-76 copy number in response to TCR engagement in the absence of presence of Nef. To this end, Jurkat CD4 T cells stably expressing a SLP-76-HaloTag fusion protein were labelled in suspension with Halo-SiR and stimulated on glass cover slides functionalised with -CD3 antibodies for activation [28][29][30] . To synchronise the activation reaction of individual cells, only cells that adhered to the cover slide within the first 3 seconds were observed and all other cells washed away.…”
Section: Quantitative Insight In the Disruption Of T Cell Receptor Si...mentioning
confidence: 99%